Efisiensi Persediaan Beras Pada Perusahaan Umum Bulog Divisi Regional Jawa Timur - Eva Yuliana Kristyaningrum; Titik Ekowati; Agus Setiyadi (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2016)
Rice is a staple food in Indonesia. Badan Urusan Logistik (BULOG) has the job of Public Service Obligation (PSO) to maintain the availability of rice in Indonesia. The objectives of this study were to 1) analyze the economic order quantity, the amount of safety stock, maximum inventory, and reorder point by Perum BULOG Regional Division of East Java; 2) analyze total inventory cost and efficiency cost of rice stock by Perum BULOG Regional Division of East Java. The research method was the case study. Purposive sampling was used to determine research location. Data were analyzed by the economic order quantity (EOQ), safety stock, maximum inventory, reorder point, total inventory cost, and cost-efficiency. Research result showed that economic order quantity at Perum BULOG Regional Division of East Java was 3,331 ton for each ordering and ordering frecuency for each years was 357 times. The amount of safety stock was 297,360.5 ton. Maximum inventory that can be managed was 300,691.5 ton. Reorder point by Perum BULOG Regional Division of East Java was 395,122.9 ton. The cost efficiency up to IDR 4,040,130.